2013
DOI: 10.1371/journal.pone.0082007
|View full text |Cite
|
Sign up to set email alerts
|

Two Randomized Trials Provide No Consistent Evidence for Nonmusical Cognitive Benefits of Brief Preschool Music Enrichment

Abstract: Young children regularly engage in musical activities, but the effects of early music education on children's cognitive development are unknown. While some studies have found associations between musical training in childhood and later nonmusical cognitive outcomes, few randomized controlled trials (RCTs) have been employed to assess causal effects of music lessons on child cognition and no clear pattern of results has emerged. We conducted two RCTs with preschool children investigating the cognitive effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 31 publications
3
97
2
5
Order By: Relevance
“…This concern highlights, however, the need for experimental studies of the relationship between musical ability and specific domains of executive functioning. There is a small body of longitudinal studies of this sort (e.g., Moreno et al, 2011;Roden et al, 2014), but so far these approaches have not investigated multiple domains of EF and have yielded somewhat mixed results (e.g., Mehr, Schachner, Katz, & Spelke, 2013;Rickard, Bambrick, & Gill, 2012;see Okada & Slevc, in press, for a review), and so more work is clearly needed. In particular, the present findings suggest the utility of investigating memory updating in longitudinal designs.…”
Section: Discussionmentioning
confidence: 99%
“…This concern highlights, however, the need for experimental studies of the relationship between musical ability and specific domains of executive functioning. There is a small body of longitudinal studies of this sort (e.g., Moreno et al, 2011;Roden et al, 2014), but so far these approaches have not investigated multiple domains of EF and have yielded somewhat mixed results (e.g., Mehr, Schachner, Katz, & Spelke, 2013;Rickard, Bambrick, & Gill, 2012;see Okada & Slevc, in press, for a review), and so more work is clearly needed. In particular, the present findings suggest the utility of investigating memory updating in longitudinal designs.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to take this into account when interpreting scores on melodic discrimination tests, instead of simply equating test scores with concepts such as musical aptitude (e.g. Hu et al, 2013;Mehr et al, 2013Mehr et al, , 2016 or melodic memory (e.g. Müllensiefen et al, 2014;Zenatti, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The AMMA constitute the most widely used melodic discrimination test in academic research, and feature in many recent studies as a measure of musical aptitude (e.g. Hu et al, 2013;Kühnis, Elmer, Meyer, & Jäncke, 2012, 2013Mehr, Schachner, Katz, & Spelke, 2013;Mehr, Song, & Spelke, 2016). The AMMA comprise 30 items, none of which include transpositions.…”
Section: Melodic Discrimination Testsmentioning
confidence: 99%
“…One may remember that brief time when we thought that all we needed in dance education was to find something comparable to the 'Mozart effect,' initially hailed by music educators as the proof of the value of music education for young children's brain development. But good scientific research must be replicable, and further studies were not able to replicate the very modest effects shown in the initial research (Carroll 2006;Mehr et al 2013). The myth of the Mozart effect, however, is perpetuated by many who have a profit to make from Mozart.…”
Section: Discussionmentioning
confidence: 99%